Sustainable Development of Healthcare System in Nepal through Social Determinants of Health - Khatiwada, Kabita (Academia Journal of Humanities & Social Sciences, 2025)
The rural populations of Nepal face geographic and economic barriers while marginalized groups encounter discrimination in healthcare. The objective of this study was to survey the healthcare associated individuals to understand the factors affecting access and development of healthcare facilities. A cross-sectional survey was conducted with the healthcare receivers and providers using a questionnaire. This study surveyed 291 individuals, including 200 patients and 91 healthcare providers. Among them, 66.5% of providers worked in private hospitals, 53% of respondents were female, and 58% of patients were from urban areas, with significantly higher private hospital utilization. Financial constraints were the primary patient barrier (48.5%), followed by lack of information (28.5%). No significant differences were found between hospitals regarding these barriers. However, female patients reported significantly higher financial constraints. In total, 44.5% of patients used government insurance, 28% private, 27% out-of-pocket, and 55.5% reported good health status. Patients perceived significantly better quality of care in private hospitals and higher rates of misbehavior from providers in government hospitals. In conclusion, the survey revealed significant disparities in healthcare access in Nepal, with financial constraints and information gaps posing major barriers, especially for women. Urban patients perceived better care in private hospitals, while reporting more misbehavior in government facilities. Therefore, addressing financial constraints through targeted findings and improving information spreading, particularly for rural populations and women, are critical steps toward equitable healthcare access.